2023
DOI: 10.2174/1573399818666220427124448
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABO Blood Groups and Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: Background: The role of the ABO blood group goes beyond immunohematology as there is accumulating evidence on its association with type 2 diabetes mellitus. However, findings regarding the relation have been contradictory and there is a need to determine the validity of claims. Objective: Evaluate the susceptibility of the ABO blood groups to type 2 diabetes mellitus. Method: The research design is a meta-analysis. An extensive search was done in PubMed, ScienceDirect, ResearchGate, and Google Scholar. Het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The exact underlying mechanisms behind this connection remain unclear and are possibly ascribed to systemic inflammatory and immune response [ 65 67 ]. Interestingly, type 2 diabetes, a known risk factor for PC, was found to partially mediate the causal effect from ABO to PC in our study, despite the controversial association between blood group and diabetes in previous reports [ 68 , 69 ]. Similarly, a retrospective study revealed a higher proportion of B blood type patients among those with long-term diabetes before PC diagnosis than that among PC patients without diabetes at diagnosis [ 70 ], which also implied the intricate interaction between ABO blood type, diabetes mellitus, and PC.…”
Section: Discussioncontrasting
confidence: 58%
“…The exact underlying mechanisms behind this connection remain unclear and are possibly ascribed to systemic inflammatory and immune response [ 65 67 ]. Interestingly, type 2 diabetes, a known risk factor for PC, was found to partially mediate the causal effect from ABO to PC in our study, despite the controversial association between blood group and diabetes in previous reports [ 68 , 69 ]. Similarly, a retrospective study revealed a higher proportion of B blood type patients among those with long-term diabetes before PC diagnosis than that among PC patients without diabetes at diagnosis [ 70 ], which also implied the intricate interaction between ABO blood type, diabetes mellitus, and PC.…”
Section: Discussioncontrasting
confidence: 58%
“…A comparative cross-sectional study, including 326 participants (163 T2DM patients and 163 age and sex-matched healthy individuals), confirmed the harmful association of blood group B with T2DM risks (OR = 1.96; 95% CI: 1.05, 3.65), compared with the non-B blood group [ 80 ]. A meta-analysis revealed blood group B was significantly associated with an increased risk of T2DM (RR = 1.05; 95% CI: 0.93, 1.18), compared with the non-B blood group [ 81 ]. Nevertheless, caution is warranted in interpreting the observed association between blood group B and T2DM risk.…”
Section: Discussionmentioning
confidence: 99%